2010
DOI: 10.1159/000321108
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Immunoassay Using Recombinant Allergens Simplifies Peanut Allergy Diagnosis

Abstract: Background: Double-blind placebo-controlled food challenge (DBPCFC) is currently considered the gold standard for peanut allergy diagnosis. However, this procedure that requires the hospitalization of patients, mostly children, in specialized centers for oral exposure to allergens may cause severe reactions requiring emergency measures. Thus, a simpler and safer diagnosis procedure is needed. The aim of this study was to evaluate the diagnostic performance of a new set of in vitro blood tests for peanut allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
102
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(137 citation statements)
references
References 65 publications
(63 reference statements)
32
102
1
2
Order By: Relevance
“…Our findings are in line with others showing that Ara h 2 is the most important peanut allergen [1,2,3,4,5,6,11,21,22]. Data about the prevalence and diagnostic value of Ara h 6 are rare, but in accordance with our results two studies showed that both peanut 2S albumins are recognized by IgE from the same patients in almost all cases and that the diagnostic accuracy of IgE specific to Ara h 6 in adults is as good as for Ara h 2 [1,7]. The study performed by Klemans et al [7] identified similar IgE levels for those two allergens when performing ImmunoCAP ISAC [1,7].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in line with others showing that Ara h 2 is the most important peanut allergen [1,2,3,4,5,6,11,21,22]. Data about the prevalence and diagnostic value of Ara h 6 are rare, but in accordance with our results two studies showed that both peanut 2S albumins are recognized by IgE from the same patients in almost all cases and that the diagnostic accuracy of IgE specific to Ara h 6 in adults is as good as for Ara h 2 [1,7]. The study performed by Klemans et al [7] identified similar IgE levels for those two allergens when performing ImmunoCAP ISAC [1,7].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings confirm observations from other peanut CRD studies that have demonstrated that this allergen panel enables the majority of peanut-allergic patients to be identified [1,18]. However, although the peanut extract was absolutely discriminative between patients with suspected peanut allergy and nonatopic controls, a positive sIgE result for peanut extract did not reflect the clinical relevance as it was also found in 75% of individuals without an apparent peanut allergy.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our study concurs with previous studies that Ara h 2 seems to be the most important peanut allergen. [5][6][7][8] Ara h 2 by ImmunoCAP as well as the ISAC test were significantly more frequently positive in peanut-allergic than in asymptomatically sensitised patients. ImmunoCAP Ara h 2 was positive in 92% of peanut-allergic patients, similar to recent studies in China [14] (87% positivity) and Japan [7] (88% Ara h 2-positive).…”
Section: Discussionmentioning
confidence: 89%
“…Component testing for peanut proteins helps differentiate between nonspecific crossreactive components such as Ara h 5, 8 and 9 and specific peanut components such as Ara h 1, 2, 3 and 6, which are heat-resistant storage proteins. Ara h 2 (2S albumin storage protein) has been shown to be the most important component in prediction of food allergy in several countries, including the UK, [5] France, [6] Japan [7] and the USA, [8] with a positive result (>0.35 kU/L) to Ara h 2 having a high predictive value for peanut allergy. In Medi terranean countries, the lipid transfer factor Ara h 9 is an important peanut allergen.…”
mentioning
confidence: 99%